PENGARUH DEBT DEFAULT, DISCLOSURE, AUDIT CLIENT TENURE, DAN AUDIT LAG TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA - Zulfikri Rahmat; Andreas '; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Going concern assumption used in the preparation of the financial statement. Operational company should be able to maintain it’s surviva. If the auditor does not believe the survival of the company business, then the matter must be presented in the audit report after the opinion paragraph. The company does not except to get a going concern opinion because it could be affect the company image. Bankruotcy would actually happen if there is no proper treatment to address the going concern issue. This study examined the effect of debt default, disclosure, audit client tenure, and audit lag on acceptance going concern audit opinion. Research sample as many as 33 real estate and property companies in Indonesia Stock Exchange period 2011-2013 with purposive sampling method. Logistic regression analysis used as a technique of data analysis and hypothesis testing. The result show empirical evidence that debt default and disclosure have a significant effect on acceptance going concern audit opinion, debt default had significant value 0,047 and disclosure had significant value 0,027. Audit client tenure and audit lag not have a significant effect on acceptance going concern audit opinion, audit client tenure had significant value 0,815 and audit lag had significant value 0,592.Keywords: debt default, disclosure, audit client tenure, audit lag and going concern audit opinion